Recent advances in electrospinning of nanofibers from bio-based carbohydrate polymers and their applications. (February 2022) - Angel, Nicole; Li, Songnan; Yan, Feng; Kong, Lingyan
Abstract: Background: Electrospinning is a simple, versatile method that employs an electrostatic force to produce fibers in the micro-to nanometer range using a wide variety of materials ranging from natural biopolymers to synthetics. Variations on the basic electrospinning set-up can be used to produce fibers demonstrating various morphological and functional properties advantageous for specific applications. Moreover, electrospun fibers created using naturally occurring polysaccharides have attracted much attention due to, but not limited to, their biological properties and sustainable sourcing. Scope and approach: In this review, common variations on the basic electrospinning set-up are briefly discussed for their benefits in fiber morphology and upscaling capabilities. In depth, electrospun fibers made from polysaccharides; specifically alginate, cellulose, chitin and chitosan, starch, pullulan, hyaluronic acid, dextran, and levan; are discussed with an emphasis on the current research direction being taken for each of these materials. Moreover, current methods to increase electrospinnability for these polysaccharides are presented as well. Key findings and conclusions: Electrospun fibers can be specifically tailored for their function by the optimization of the electrospinning process and spinning dope. However, before the electrospinning process can be successfully upscaled on an industrial or commercial level, it is important to determine an effective method for increasing the rate of fiber production and, generally in the case of polysaccharides, increasing electrospinnability. Biopolymer fibers, specifically, demonstrate high potential in the biomedical field due to their biodegradability and compatibility properties. Highlights: Electrospinning technique is simple, versatile, and scalable. Nanofibers successfully electrospun from various bio-based carbohydrate polymers. Biopolymer nanofibers show many advantages for food and related applications.